2007
DOI: 10.1021/la063039b
|View full text |Cite
|
Sign up to set email alerts
|

Superior Water Repellency of Water Strider Legs with Hierarchical Structures:  Experiments and Analysis

Abstract: Water striders are a type of insect with the remarkable ability to stand effortlessly and walk quickly on water. This article reports the water repellency mechanism of water strider legs. Scanning electron microscope (SEM) observations reveal the uniquely hierarchical structure on the legs, consisting of numerous oriented needle-shaped microsetae with elaborate nanogrooves. The maximal supporting force of a single leg against water surprisingly reaches up to 152 dynes, about 15 times the total body weight of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
288
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 350 publications
(305 citation statements)
references
References 36 publications
9
288
2
6
Order By: Relevance
“…79 The now commonly accepted meaning of a superhydrophobic surface is a surface on which the water (advancing) contact angle is at least 150°, and the contact angle hysteresis as well as the sliding (or rolling off) angle (sliding/rolling angle is the minimum angle of sloped solid at which water (liquid) drop rolls off the surface) do not exceed 5-10° (Table 2). Although currently superhydrophobic surfaces are inspired by biological specimens, [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] the early research was inspired by the practical need to enhance coating repellency of water and snow. 98,99 These days, superhydrophobic coatings are manufactured by chemical, physical and/or mechanical modifications of both organic and inorganic materials.…”
Section: 78mentioning
confidence: 99%
“…79 The now commonly accepted meaning of a superhydrophobic surface is a surface on which the water (advancing) contact angle is at least 150°, and the contact angle hysteresis as well as the sliding (or rolling off) angle (sliding/rolling angle is the minimum angle of sloped solid at which water (liquid) drop rolls off the surface) do not exceed 5-10° (Table 2). Although currently superhydrophobic surfaces are inspired by biological specimens, [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] the early research was inspired by the practical need to enhance coating repellency of water and snow. 98,99 These days, superhydrophobic coatings are manufactured by chemical, physical and/or mechanical modifications of both organic and inorganic materials.…”
Section: 78mentioning
confidence: 99%
“…Barthlott et al also clearly understood that the micro-and nano-structures of the plants surfaces define their eventual wetting properties, in accordance with the Cassie-Baxter and Wenzel models (discussed in detail in the previous Section) [49][50][51]. Since Barthlott et al reported the extreme water repellency of the lotus, similar phenomena were reported for a diversity of biological objects: water strider legs, as well as bird and butterfly wings [52][53][54][55].…”
Section: Superhydrophobicitymentioning
confidence: 57%
“…All the phenomenon was called superhydrophobicity and natural and artificial surfaces characterized by an apparent contact angle larger than 150° are referred to as superhydrophobic [9,10,[52][53][54][55]. It should be emphasized that high apparent contact angles observed on a surface are not sufficient for referring it as superhydrophobic [56][57][58].…”
Section: Superhydrophobicitymentioning
confidence: 99%
See 1 more Smart Citation
“…7 Surface wrinkle is one of the promising ways to obtain micro structures via a bottom-up approach. 8 Micro wrinkles have many potential applications such as lab-on-a-chip, 9 micro-electro-mechanical systems (MEMS), 10 drug delivery carrier, 11 biosensing, 12 and so on. The surface wrinkle forms on a film comprised of multi-layered structures with different mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%